Revealing the fake initial coulombic efficiency of spinel/layered Li-rich cathode materials. (1st July 2020) - Wu, Hualong; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Peng, Wenjie; Hu, Qiyang; Yan, Guochun; Wang, Jiexi
Abstract: Synthesizing spinel/layer Li-rich materials (SLLRs) is a promising way to improve the electrochemical performance of Li-rich material. In this work, the influence of introducing spinel phase into layered one on the coulombic efficiency is studied by electrochemical method. During CV testing, the composite exhibits no oxidation peak around 2.5–3.0 V when it starts with positive scanning, while demonstrates a reduction peak at ∼2.57 V as it begins with negative scanning. This means the spinel phase formed during the synthetic process is lithium-deficient, consuming lithium from lithium metal anode during discharge in Li-half cell. Charge-discharge results show that this spinel phase contributes to extra capacities when cells are discharged below 3.0 V, leading to a higher initial coulombic efficiency (ICE) of SLLRs in half cells. However, when tested in full cell using graphite as anode, ICE of SLLRs equals to that of Li-rich material while the capacity is lower. This is because that the graphite anode in full cell is unable to provide extra lithium ions and to compensate lithium deficiency of cathode material. Strategy like electrochemical pre-lithiation is suggested to improve the electrochemical performance of SLLRs in full cell. Highlights: The introduced spinel phase into layered one was lithium-deficient. The fake high ICE in spinel-layer composite in half-cell was revealed by CV. Electrochemical pre-lithiation promoted the application of SLLR in full cell.